Civic and Political Participation of European Youth: Fair Measurement in Different Cultural and Social Contexts - Enchikova, Ekaterina; Neves, Tiago; Mejias, Sam; Kalmus, Veronika; Cicognani, Elvira; Ferreira, Pedro D. (Frontiers in Education, 2019)
Civic and political participation (CPP) is often routinely operationalized through the same questions, as can be found in many related studies. While questions can be adapted in accordance with the research purposes, their psychometric properties are rarely addressed. This study examines the potential methodological problems in the measurement of CPP, such as the conflict between construct validity and measurement invariance, as well as unequal item functioning between some groups of people. We use the Rasch model to test 18 CPP questions for their relevance for the European youth population and to study differential item functioning between groups based on (1) age, (2) gender, (3) economic satisfaction and (4) country of living. We discovered that CPP questions are strongly connected with the cultural and social context and can discriminate against some groups of people. The results can be used in future studies to build fair and valid scales of CPP.